The New Partnership for Africa’s Development and Regional Integration in Africa: Challenges and Prospects - Unya , Ikenna Ukpabi; Okorie , Martha (Kashere Journal of Politics and International Relations, 2024)
The New Partnership for Africa’s Development (NEPAD) is the African socio-economic development plan based on a new partnership between African States and their development partners, especially the highly industrialized countries of the West. It is an initiative geared towards overcoming Africa’s problems of underdevelopment, poverty, undemocratic regimes and poor cooperation among African states. However, since the inception of NEPAD, much economic integration had not taken place among the African states. Hence, the study sets to examine why NEPAD has not made considerable impact in integrating the sub-regional economic groups in Africa. The study is basically qualitative. It utilized existing literatures on African regional development in seeking understanding about NEPAD. The findings reveal that unlike the European Union (EU) and the Association of Southeast Asian Nations (ASEAN), regional organizations whose citizens are familiar with the workings of their economic mechanisms, many citizens in Africa have fuzzy knowledge of the African Union (AU) and the NEPAD. The study concludes by recommending that African leaders should involve the civil society, private organizations and ordinary people in the activities of NEPAD in order to create the necessary ownership of the project.